Optimizing Migration of Applications Through Effective Risk Measurement - Maniah, Maniah; Mulyati, Erna; Hamidin, Dini (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2025)
Cloud Computing is a service that provides network storage space and computer resources using an internet connection as an access medium. The process of migrating to cloud computing goes through several stages sequentially and continuously, but sometimes the process of migrating to cloud computing faces obstacles or even failure, this is of course a risk for cloud service users. For this reason, before migrating to the cloud, it is necessary to prepare well, because if not, it will cause losses which will have a risk impact on the company. An effort to minimize risks for cloud service users is to carry out a risk assessment. The aim of this research is to create a model for risk assessment of logistics business applications in cloud migration. The risk value measurement model developed adopts the risk management model from the ISACA Risk IT Framework, the risk management process part of the ISO 31000 standard and adopts the phases of the OCTAVE method. Based on the method of measuring risk values from the results of this research, companies will know how much risk is likely to arise due to the use of cloud data centers, so that risk mitigation can be carried out immediately. This will have an impact on increasing the security of cloud services, and this is the main thing in increasing public confidence in using cloud services.